Digital Preservation of Real World Objects Using Photogrametry from Digital Image - Moch Fachri; Nur Hikmah (Institute of Computer Science (IOCS), 2020)
One form of objects preservation is by converting real world objects into digital form. This allows historical information from these relics to be preserved even if due to some reason, the physical objects have disappeared. This research develops a digital image processing technology called photogrammetry to create three-dimensional models of real world objects. The use of photogrammetry is intended for digital preservation of real world objects which is formed in a 3D Reality Capture. The results we show that the digital information of real world objects can be presented in a virtual world and the data can be stored for preservation and future use.